2009
DOI: 10.1016/j.biomaterials.2009.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic shear-influenced collagen self-assembly

Abstract: The ability to influence the direction of polymerization of a self-assembling biomolecular system has the potential to generate materials with extremely high anisotropy. In biological systems where highly-oriented cellular populations give rise to aligned and often load-bearing tissue such organized molecular scaffolds could aid in the contact guidance of cells for engineered tissue constructs (e.g cornea and tendon). In this investigation we examine the detailed dynamics of pepsin-extracted type I bovine coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 67 publications
3
79
0
Order By: Relevance
“…Previously, we have shown that hydrodynamic shear stress is capable of producing relatively aligned arrays of collagen fibrils in a microfluidic device [25]. In that study, “hooked” fibrils formed against the flow field due to surface interactions that competed with shear-induced collagen self-assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that hydrodynamic shear stress is capable of producing relatively aligned arrays of collagen fibrils in a microfluidic device [25]. In that study, “hooked” fibrils formed against the flow field due to surface interactions that competed with shear-induced collagen self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…thinnest chambers) the flow in this system was not strong enough to influence the organization of the individual collagen molecules but could influence the direction of larger aggregates (e.g. dimers and trimers) which spontaneously self-assemble under physiological conditions [25]. Thus the shear-flow technique is not suitable for assembling collagen layers with uniform fibril alignment mimetic of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…6, for all the test peptides, there was an almost hyperbolic increase in radical scavenging and chelating activity with increasing concentration. The peptides acted as potent antioxidative agents at lower concentrations but the activity asymptotically approached a maximum of 70 % at higher concentrations, probably due to the inherent recoiling nature of collagen type I peptides [43]. Upon comparison of the EC 50 values the scavenging activity was found to be in the given order, E1 followed by F3, E3 and F2.…”
Section: Effect Of Concentration On Antioxidative Activity Of Purifiementioning
confidence: 95%
“…However, at concentrations higher than 2 g·mL −1 , peptide binding decreased and cells were observed to adhere to collagen, an apparently unusual effect that arises due to the recoiling tendency of collagen-like peptides. At higher amounts, most collagen peptides recoil to each other forming transient helices (Saeidi et al 2009), and mostly remain unavailable for binding with cellular receptors. Free binding sites of the cellular receptors attach to collagen instead, increasing the observed cell count.…”
Section: Bioactivity Assessment Of Purified E1 and C2mentioning
confidence: 98%